Thoracoscopic approach for massive thymic hyperplasia in an infant: Case report and literature review - Jiao, Jinghua; Yu, Jie; Chen, Chenghao; Chen, Tian; Zheng, Tiehua; He, Lejian; Zeng, Qi (Frontiers in Pediatrics, 2023)
Introduction： Massive thymic hyperplasia (MTH) is a very rare entity, with fewer than 20 cases reported in the literature in infancy. Most patients have respiratory symptoms and the enlarged thymus gland occupies one side of the thoracic cavity. Posterolateral thoracotomy or median sternotomy is the main treatment for MTH in infants. We report a case of an infant with MTH in which the enlarged thymus occupied his bilateral thoracic cavity and he underwent video-assisted thoracoscopic surgery (VATS). In addition, we reviewed and summarized the relevant literature. Case Report： A 4-month-old boy was admitted to the hospital with no apparent cause of dyspnea for 18 days, with cough and sputum. On examination, the patient was found to have cyanotic lips, diminished breath sounds in both lungs, and a positive three concave sign. There was no fever or ptosis. Preoperative imaging showed large soft tissue shadows in the bilateral thoracic cavity, with basic symmetry between the right and left sides. Tumor markers were within the normal range. Ultrasound-guided fine needle biopsy showed normal thymic structures with no evidence of malignancy. As his symptoms worsened, he eventually underwent unilateral thoracic approach video-assisted thoracoscopic exploratory surgery, during which a large mass occupying the bilateral thoracic cavity was removed in a separate block and part of the thymus in the left lobe was preserved. Pathological examination confirmed true thymic hyperplasia (TTH). No relevant complications occurred at the 2-month postoperative follow-up. Conclusion： In infants, MTH occupying the bilateral thoracic cavity can produce severe respiratory and circulatory symptoms due to occupying effects. Although a definitive preoperative diagnosis is sometimes difficult, after combining computed tomography (CT) and fine needle biopsy to exclude evidence of other malignancies, the enlarged thymus occupying the bilateral thoracic cavity can be resected via VATS. Whether the enlarged thymus occupies the bilateral thoracic cavity and the size of the thymus are not absolute contraindications to thoracoscopic surgery. The method is safe, feasible, and minimally invasive to the patient.